Periodontitis-Derived Dark-NETs in Severe Covid-19 - Vitkov, Ljubomir; Knopf, Jasmin; Krunić, Jelena; Schauer, Christine; Schoen, Janina; Minnich, Bernd; Hannig, Matthias; Herrmann, Martin (Frontiers in Immunology, 2022)
The frequent severe COVID-19 course in patients with periodontitis suggests a link of the aetiopathogenesis of both diseases. The formation of intravascular neutrophil extracellular traps (NETs) is crucial to the pathogenesis of severe COVID-19 and late-onset periodontitis. Periodontitis is characterised by an increased level of circulating NETs, a propensity for increased NET formation, delayed NET clearance and low-grade endotoxemia (LGE). The latter has an enormous impact on innate immunity and susceptibility to infection with SARS-CoV-2. LPS binds the SARS-CoV-2 spike protein and this complex, which is more active than unbound LPS, precipitates massive NET formation. Thus, exaggerated circulating NET formation is the common denominator in both COVID-19 and periodontitis and other diseases with low-grade endotoxemia like diabetes, obesity and cardiovascular diseases (CVD) also increase the risk to develop severe COVID-19. Here we discuss the role of propensity for increased NET formation, DNase I deficiency and low-grade endotoxaemia in periodontitis as exacerbatingaggravating factors for the severe course of COVID-19 and possible strategies for the attenuationdiminution of exaggerated increased levels of circulating periodontitis-derived NETs formation in late-onset periodontitis as comorbidity of COVID-19 with periodontitis comorbidity.